Photonic Integrated Circuits for Communication Systems - J. Chovan; F. Uherek (Radioengineering, 2018)
Photonic Integrated Circuits allow to meet the increasing demand of communication systems for internet which is growing at about 40% per year. This growth is driven mainly by increasing video traffic in the internet network. This growth is now further accelerated by mobile access, with video clients shipping on an all smart phones and tablets, enabling video to be consumed more conveniently via network connections anywhere and anytime. This paper reviews several material platform of photonic integrated circuits a compares their performance. This paper also describes the new approaches in the design and fabrication of optical transceivers based on photonic integrated circuits for next terabit era.